Eficácia da Buspirona e da Venlafaxina na perturbação de ansiedade generalizada - João Marques Teixeira (2004)
This study evaluates both buspirona and venlafaxina efficacy in general anxiety disorder (GAD), and its consistency 6 months after treatment discontinuation. The differential efficacy of both substances (alone or in association with relaxation) regarding trait and state anxiety perturbation in the context of GAD was also evaluated. One hundred and ten patients with GAD were randomly distributed by 5 different groups: group 1 received 75 mg/day of venlafaxina extended release form; group 2 received 30 mg/day of buspirona; group 3 received relaxation training; group 4 received 75mg/day of venlafaxina extended release form plus relaxation training and, finally, group 5 eceived 30 mg/day of buspirone plus relaxation training. Patients were evaluated regarding anxiety levels by State and Trait Anxiety Inventory. Results suggested a strong positive and sustained effect on decreasing anxiety levels by the different therapeutic strategies used. Furthermore, results also suggested that buspirone (alone or associated to relaxation) was more effective regarding trait anxiety perturbations, and venlafaxina was more effective concerning state anxiety perturbations.